Analysis of anticancer drug associated adverse reactions in depressive patients from vigibase - Chrétien, Basile; Dolladille, Charles; Nishida, Kazuki; Aleksić, Branko; Alexandre, Joachim; L'Orphelin, J.‐M. (Scientific Reports, 2025)
Depressive symptomatology is prevalent among oncology patients and may influence the perception of adverse drug reactions (ADRs) to anticancer drugs. Understanding this relationship is crucial for optimizing treatment strategies and improving ADR management. This pharmacovigilance study analyzed VigiBase® data from 1968 (year of its establishment) to 2024. Focusing on reports involving antineoplastic or immunomodulating agents, a case/non-case disproportionality analysis was conducted to assess the reporting and seriousness of ADRs in patients receiving antidepressants. Multivariable analyses were performed for all ADRs and the most frequently reported ADRs. Reporting Odds Ratios (RORs) were considered significant if the 95% credible interval lower bound exceeded 1. Among 8,804,863 reports, 428,102 involved patients receiving antidepressants. Antidepressant use was associated with a higher likelihood of serious ADRs reporting(58%vs45%; adjusted-ROR:1.78, 95%CI:1.76–1.79). Increased reporting was observed for most tested ADRs, including fatigue(ROR:2.19, 95%CI:2.13–2.25), pain(ROR:2.79, 95%CI:2.69–2.89), and headache(ROR:2.56, 95%CI:2.46–2.62). The timing of antidepressant initiation did not significantly impact ADR reporting. Antidepressant use in oncology patients is associated with increased ADR reporting and seriousness, emphasizing the need for heightened clinical vigilance. Effective management of depressive symptomatology may improve ADR perception, treatment adherence, and patient well-being. Prospective studies are required to confirm these findings and inform targeted interventions.